AMBIENTE JOYCE (2016)
Currently, the most common programming languages are of sequential and these languages are running process after another, which implies a limitation, so it is able to manage just one process at the same time. In case that you need work with multiple processes at the same time, exist the concurrent programming languages, in contrast to the sequential languages, they support the simultaneity in the execution of multiple tasks. This research seeks meeting a need because there are not technologies to teach the concurrency in deep, so the progress of this work is based on the contribution of the massive development of multiprocessor systems and the use of languages concurrent programming.